Industrial and Commercial Applications of Smart Structures Technologies 2008 2008
DOI: 10.1117/12.775929
|View full text |Cite
|
Sign up to set email alerts
|

Development of a ¼-scale NiTinol actuator for reconfigurable structures

Abstract: Wind Tunnel tests of a NiTinol based actuator have been conducted for the reconfigurable rotor blade program. The purpose of the test was to demonstrate the potential to improve rotorcraft performance by optimizing the configuration of major structures in flight. The actuator is integrated into the rotor blade as a structural element controlling blade twist. A three-blade scale rotor was tested in a Boeing wind tunnel. The tests validated actuator design and performance by demonstrating simultaneous blade twis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The authors have also demonstrated a method for training a two-way shape memory effect into the material, where strains of 3% were achieved. In 2008, several other investigations reported on the shape control of a morphing structure (rotor blade) using tubes [30][31][32]. This design was tested in a wind tunnel, and according to the authors, it provided full twist of the blade tip without any measurable loss of performance.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have also demonstrated a method for training a two-way shape memory effect into the material, where strains of 3% were achieved. In 2008, several other investigations reported on the shape control of a morphing structure (rotor blade) using tubes [30][31][32]. This design was tested in a wind tunnel, and according to the authors, it provided full twist of the blade tip without any measurable loss of performance.…”
Section: Introductionmentioning
confidence: 99%
“…Dating back to the 1960s, this specific composition has been investigated as a function of heat treatments/ageing [3][4][5][6], thermomechanical processing of ingot and powder samples [7,8], and occasional theoretical studies [9]. Depending on the specific processing parameters, this alloy can be tailored for actuation purposes [10][11][12][13], tribological applications [14], tools and cutlery [3,15,16], and biomedical surfaces [17], while derivative alloys are being explored in attempts to optimize properties for some of these applications [18].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an RRB project was developed to integrate SMA actuators into the rotor blade construction of the aircraft. This project utilizes SMA actuators to optimize the traditional structural configuration and significantly enhance performance [ 73 ]. The results of the RRB project showed that the small protruding structure on the rotor blades can effectively reduce the noise caused by the blade–vortex interaction, but at the same time, it will also reduce the performance of the overall structure due to increased resistance [ 74 ].…”
Section: Shape Memory Materialsmentioning
confidence: 99%